PENGARUH MODEL PEMBELAJARAN OPEN ENDED TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V MATA PELAJARAN MATEMATIKA DI MI - Nurhaningtyas Agustin; Lafifatun Ni’mah (PREMIERE : Journal of Islamic Elementary Education, 2020)
Mathematics is one of the subjects that trains students to think critically, logically, analytically, systematically, and creatively. One of the regulations of the Minister of Nation Education No.23 of 2006 years, about “graduate competency standards” is to have the ability to cooperate. One way to develop students’s critical thinking skills is to apply student oriented learning with open learning, Open Ended. The method in this study is an experimental method by applying an Open Ended learning model. The purpose of this study was to obtain data or information about the influence and general picture of students critical thinking skills after the application of Open Ended learning in teaching and learning in the classroom. In addition to get an overview of students respones to the application of Open Ended. This study took the population class V MI Al-Falahiyah Kedungrejo-Kerek-Tuban lesson years 2019/2020. This study uses the population as a score of data because the number of students studied is less than 100 students. Namely fifth grade students, amuting to 20 students. The instruments used as data collection were questionnaires and test of mathematical critical thinking skills in fraction subjects. The statistical test used was a t-test with a pre test and post test one group design. Students whos responded to learning with who Open Ended model with a score range’s of 25-27by 10%, a range scores of 28-30 by 15%, a range scores 31-33 by 30%, a range scores of 34-36 by 15%, and 37-39 by 30%. With 11 students who responded well, and 9 students who responded very good, to the Open Ended learning model. Hypothesis test results with the t-test t hitung > t tabel (2,109>2,029). While the average value of students mathematic critical thinking ability of students is categorized as moderate or sufficient.